2014
DOI: 10.1007/s12672-014-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Initiated Estradiol Signaling of Epithelial-Mesenchymal Transition-Associated Mechanisms Through Regulation of Tight Junctions in Human Breast Cancer Cells

Abstract: Tumor cells utilize inappropriate epithelialmesenchymal transition (EMT) mechanisms during the invasive process. It is becoming increasingly clear that estradiol (E2) induces breast cancer cell progression and enhances EMT; however, the mechanisms associated with this are unclear. We investigated the role of E2 on the expression and intracellular localization of the tight junction (TJ)-associated proteins, zonula occluden 1 (ZO-1), ZO-1-associated nucleic acid binding (ZONAB), and occludin, on the activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…The role of chlamydia-inducible, cytokines such as TNF-alpha and TGF-beta in EMT and fibrosis has been well established [ 86 ]. Thus, the ability of estrogen to induce EMT involving miRNA alterations [ 87 ], and our results showing that chlamydia induced EMT and estrogen receptors, would suggest that chlamydia may induce EMT via the estrogen receptor-signaling pathway. Consistent with the miRNA profiles and up-regulation of pro-EMT proteins, our results further showed that the chlamydial down-regulated proteins are those that maintain epithelial integrity, support reproductive fertility, control fibrosis and act as tumor suppressors.…”
Section: Discussionmentioning
confidence: 88%
“…The role of chlamydia-inducible, cytokines such as TNF-alpha and TGF-beta in EMT and fibrosis has been well established [ 86 ]. Thus, the ability of estrogen to induce EMT involving miRNA alterations [ 87 ], and our results showing that chlamydia induced EMT and estrogen receptors, would suggest that chlamydia may induce EMT via the estrogen receptor-signaling pathway. Consistent with the miRNA profiles and up-regulation of pro-EMT proteins, our results further showed that the chlamydial down-regulated proteins are those that maintain epithelial integrity, support reproductive fertility, control fibrosis and act as tumor suppressors.…”
Section: Discussionmentioning
confidence: 88%
“…Epithelial–mesenchymal transition (EMT), a feature of metastatic cells, has previously been described in the context of tumor budding [ 22 ] and could be consistent with the observed association to both LVI and lymph node positivity but requires further analysis. A recent report also demonstrated that estrogen is involved in EMT in breast cancer cell lines with stem cell properties [ 23 ] and it was shown that estrogen is involved in disruption of tight-junction and increased cell motility [ 24 ]. We suspect that ER-positive tumors with high tumor budding may be undergoing a high degree of EMT and therefore have more metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of these observations is not clear. However, it was recently reported that oestrogen is involved in EMT in breast cancer cell lines with stem cell properties ( Sun et al , 2014 ) and that oestrogen is involved in disruption of tight junction and increased cell motility ( Sanchez et al , 2010 ; Jiménez-Salazar et al , 2014 ). Therefore, this may suggest that ER-positive tumours with high tumour budding may be undergoing a higher degree of EMT and as a result more metastatic potential.…”
Section: Discussionmentioning
confidence: 99%